Application of Artificial Intelligence in Quality Analysis and Weight Estimation of Green Coffee Beans - Pham Minh , Khan; Le Hoanh, Su (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Vietnam is the second largest country in the world in terms of coffee export volume, in order to maintain this achievement, the quality of green coffee beans plays a very important role. Coffee exporters need to control the quality of coffee from the stage of purchasing each consignment at the household to preliminarily processing at the factory and exporting. However, the quality control of green coffee requires expertise and is being done manually, so it takes time, effort and cost for the exporters. Therefore, the objective of this study is to build a process, design an algorithm to apply artificial intelligence (AI) to analyze the quality and estimate the weight (ULKL) of green coffee beans automatically and quickly and reduce costs. The study was carried out by collecting and labeling samples of coffee bean data according to 12 types of beans, training the model with Yolov5 in object recognition, OpenCV open-source image processing technology, CNN (Convolutional) algorithm Neural Networks) in image processing for classification and weight estimation of each type of coffee bean. The research results show that the applied algorithm models give highly reliable results, which can be applied in practice.
Keywords: Coffee classification; Weight estimates; CNN; Image processing; Artificial Intelligence